Probability, statistics, and stochastic processes for engineers and scientists - Haghighi, Aliakbar Montazer; Wickramasinghe, Indika Rathnathungalage (Boca Raton : CRC Press, 2020)
Featuring recent advances in the field, this new textbook presents probability and statistics, and their applications in stochastic processes. This book presents key information for understanding the essential aspects of basic probability theory and concepts of reliability as an application. The purpose of this book is to provide an option in this field that combines these areas in one book, balances both theory and practical applications, and also keeps the practitioners in mind. Features Includes numerous examples using current technologies with applications in various fields of study Offers many practical applications of probability in queueing models, all of which are related to the appropriate stochastic processes (continuous time such as waiting time, and fuzzy and discrete timelike the classic Gambler's Ruin Problem) Presents differentcurrent topics like probability distributions used in real-world applications of statistics such as climate control and pollution Different types of computer software such as MATLAB, Minitab, MS Excel, and R as options for illustration, programing and calculation purposes and data analysis Covers reliability and its application in network queues
Preliminaries. Basics of Probability. Random Variables and Probability Distribution Functions . Descreptive Statistics. Inferential Statistics. Nonparametric Statistics. Stochastic Processes. Appendix. Bibliography.
OCLC-licensed vendor bibliographic record.
Keywords: Engineering -- Statistical methods; Stochastic analysis; MATHEMATICS / Probability & Statistics / Bayesian Analysis; TECHNOLOGY / Engineering / Industrial; TECHNOLOGY / Operations Research